Canadian Wildfire Evacuation Data - Tepley, Alan J.; Parisien, Marc-André; Wang, Xianli; Oliver, Jacqueline; Flannigan, Mike D. (Zenodo, 2021)
Database of wildfire evacuations across the forested regions of Canada from 1980 to 2019. The database provides the data evaluated in the publication titled, “Wildfire evacuation patterns and syndromes across Canada’s forested regions,” which was submitted to Ecological Applications in November, 2021. The data file provides information on each documented wildfire evacuation and the characteristics of the fire that most likely led to the evacuation. The information on wildfire evacuations includes the location, the estimated population, whether it is a First Nations reserve, the estimated number of evacuess in five broad categories, the date that the evacuation order was issued, the date the order ended, and the reason why the order was issued. This information was compiled from more than 2,000 news reports, which were found using keyword searches in the Canadian Reference Centre, Canadian Newsstand, Canadian Research Index, Canadian Business and Current Affairs, and Proquest. Additional data were acquired by contacting provincial and territorial emergency management agencies and the Royal Canadian Mounted Police, as described in Beverly and Bothwell (2011; Wildfire evacuations in Canada 1980-2007; Natural Hazards 59:571-596). The fire characteristics include the fire size, ignition source, day of year on which it was first reported, and the database from which these values were derived. The databases for the original fire data include the National Burned Area Composite (NBAC), the National Fire Database (NFDB) fire polygon data, and the NFDB fire point data. The fire databases are available to the public at the CWFIS datamart (https://cwfis.cfs.nrcan.gc.ca/datamart). : The database was updated and revised under funding from two grants to the Canadian Safety and Security Program (CSSP-2016-CP-2286 and CSSP-2018-TI-2406), awarded to Xianli Wang.